Optimizando el mejoramiento del Arroz: Plataforma de avance generacional rápido en el HIAAL - Torres, Juanita; Carabali, Silvio James; Alvarez, Maria Fernanda (2024)
The Rapid Generation Advancement (RGA) Platform has been established with the primary purpose of accelerating the fixation process of improved lines for subsequent selection in breeding programs. This approach aims to develop fixed improved lines in less time, generating new parental combinations with the necessary traits to ensure crop stability and profitability. Reducing the time required for breeding processes and improving the precision in selecting improved lines are key parameters that ensure an increase in the rate of genetic gain.